Higher education in Turkey: responding to sustainable development agenda - Cihat, Atar; Abdul Rahman, Shukran (IIUM Press, International Islamic University Malaysia, 2019)
The study aims to review the literature that analyses the history and current situation of Higher Education (HE), henceforth known as HE, in Turkey and to review HE agenda of the Government of Turkey in order to identify the extent to which it has responded to the sustainable development agenda. This paper recommends ways to improve and develop HE in Turkey so as to make it a significant sector which prepares its stakeholders to achieve sustainable development goals (SDGs). Multiple sources of information: documents on the agenda of Turkey with regard to the objectives of HE; the findings of previous studies undertaken on different aspects of Turkish HE system; and documents prepared by organizations such as YÖK (Turkish Higher Education Council), MEB (Turkish Ministry of National Education) and the World Bank. The analysis of relevant literature suggests that Turkey aims to upgrade the HE system in line with its goals of becoming a more powerful player in the world. The initiatives to enhance enrolment of students at HE institutions; strengthen HE Education Curriculum, internationalise the Turkish HE are in line with the directions that support the attainment of SDGs. The findings provide an account of the HE system in Turkey, both strengths and weaknesses. It enhances understanding on the current situation of HE in Turkey vis a vis the Sustainable Development Goals. The study does not only describe the Turkish HE system, but it provides a case which can be used by HE researchers to study HE in different contexts